Climate change in South Asia : politics, policies and the SAARC - Majaw, Baniateilang (Oxon : Routledge, 2021)
"This volume studies the challenges of climate change in South Asia and examines the role of the South Asian association for regional cooperation (SAARC) in addressing them. It highlights the dangers posed by climate change in South Asia and underlines the need to strengthen and intensify regional cooperation to preserve, protect and manage the diverse and fragile Eco-systems of the region. The book examines policies and initiatives of the SAARC in tackling these issues and also analyzes their implementation by member countries. comprehensive and topical, this volume will be useful for scholars and researchers of South Asian studies, environmental Studies, climate change studies, public policy and governance, development studies, international relations, regional cooperation, and political studies. It will also be of importance to policymakers and NGOs working in this field."--
Keywords: Climate changes--South Asia; Environmental change--South Asia